The Influence of Kinemaster Application-Based Learning Media and Learning Environment on Student Learning Motivation at SD Katolik 1 Santo Yohanes Tomohon - Afrilia Asari Lengkong; Harol R Lumapow; Widdy H.F. Rorimpandey (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study aims to analyze the influence of KineMaster application-based learning media and the learning environment on student learning motivation at SD Katolik 1 Santohanes Tomohon. The development of digital technology encourages the use of innovative and interactive learning media to improve the quality of the teaching and learning process. The KineMaster application allows teachers to present material in an attractive audio-visual form, which can increase students' attention and interest. In addition, a conducive learning environment, both at school and at home, plays a role in shaping students' enthusiasm and motivation to learn. This study uses a quantitative approach with a survey method. Data collection was carried out through the distribution of questionnaires to students as respondents. The data was analyzed using regression tests to determine the influence of each variable, both partially and simultaneously. The results of the study show that KineMaster application-based learning media has a positive and significant effect on students' learning motivation. The learning environment also has a positive and significant effect on learning motivation. Simultaneously, these two variables have a significant influence on increasing student learning motivation. Thus, the use of KineMaster application-based learning media, supported by a conducive learning environment, can be an effective strategy in increasing student learning motivation.